Reappraisal of endometrial thickness for the detection of endometrial cancer in postmenopausal bleeding: a retrospective cohort study. (20th March 2015) - Wong, AS‐W; Lao, TT‐H; Cheung, CW; Yeung, SW; Fan, HL; Ng, PS; Yuen, PM; Sahota, DS
Abstract : Objective: To estimate the accuracy of transvaginal ultrasound (TVS) measurement of endometrial thickness (ET) in diagnosing endometrial cancer in postmenopausal women with vaginal bleeding (PMB). Design: Retrospective cohort study. Setting: One‐stop PMB clinic in a Hong Kong teaching hospital. Population: A cohort of 4383 women with PMB. Methods: Transvaginal ultrasonic measurement of ET and endometrial biopsies were obtained in women presenting with PMB between 2002 and 2013. Endometrial histology was used as the reference standard to calculate accuracy estimates. Main outcome measures: Accuracy data for TVS ET presented as sensitivity, specificity, and area under the receiver operator characteristic (ROC) curve. Results: Endometrial cancer was diagnosed in 3.8% of women. The median ET in those with endometrial cancer was significantly higher than those with benign conditions (15.7 versus 3.2 mm, P < 0.001). The area under the ROC curve was 0.92 (95% CI 0.89–0.94). The sensitivity for the detection of endometrial cancer at 3‐, 4‐, and 5‐mm cut‐offs were 97.0% (95% CI 94.5–99.6%), 94.1% (95% CI 90.5–97.6%), and 93.5% (95% CI 89.7–97.2%), respectively. The corresponding estimates of specificity at these thresholds were 45.3% (95% CI 43.8–46.8%), 66.8% (65.4–68.2%), and 74.0% (72.7–75.4%). Conclusions: Transvaginal ultrasound using a 3‐mm cut‐off has high sensitivity for detecting endometrial cancer and can identify women with PMB who are highly unlikely to have endometrial cancer, thereby avoiding more invasive endometrial biopsy.